Wideband dual circularly polarized beam‐scanning array for Ka‐band satellite communications. Issue 8 (August 2017) - Zhang, Long; Gao, Steven; Luo, Qi; Li, Wenting; Li, Qingxia
Abstract: This article presents a wideband dual circularly polarized (CP) array which has two independent beams in orthogonal circular polarizations and the two beams can scan to ±23° individually. The proposed array consists of stacked patches fed by 90° hybrid couplers. To achieve two independent beams, the beam‐forming networks (BFNs) for the left‐hand circular polarization (LHCP) beam and right‐hand circular polarization (RHCP) beam are printed on two separate layers with ground plane between them. This arrangement facilitates the integration of the BFNs and reduces the fabrication complexity. Two prototypes with different beam‐scanning angles are fabricated and measured. The measured results confirm that the array achieves good impedance matching, larger than 20 dB isolation and smaller than 3 dB axial ratio (AR) from 27 to 30 GHz when the array scans to ±23°. Due to the independent beam‐scanning ability, high isolation between the LHCP and RHCP beams and the wide bandwidth, the proposed array is promising for high data‐rate Ka‐band satellite communications which utilize polarization diversity.